Self-stigma in borderline personality disorder – cross-sectional comparison with schizophrenia spectrum disorder, major depressive disorder, and anxiety disorders - Grambal A; Prasko J; Kamaradova D; Latalova K; Holubova M; Marackova M; Ociskova M; Slepecky M (Neuropsychiatric Disease and Treatment)
Ales Grambal,1 Jan Prasko,1 Dana Kamaradova,1 Klara Latalova,1 Michaela Holubova,1,2 Marketa Marackova,1 Marie Ociskova,1 Milos Slepecky3 1Faculty of Medicine and Dentistry, Department of Psychiatry, Palacky University Olomouc, University Hospital Olomouc, Olomouc, 2Department of Psychiatry, Hospital Liberec, Liberec, Czech Republic; 3Faculty of Social Science and Health Care, Department of Psychology Sciences, Constantine the Philosopher University, Nitra, Slovak Republic Introduction: Self-stigma arises from one’s acceptance of societal prejudices and is common in psychiatric patients. This investigation compares the self-stigma of a sample of patients with borderline personality disorder (BPD), schizophrenia spectrum disorder (SCH), major depressive disorder (MDD), bipolar affective disorder (BAD), and anxiety disorders (AD) and explores of the self-stigma with the subjective and objective measures of the severity of the disorder and demographic factors. Methods: The total of 184 inpatients admitted to the psychotherapeutic department diagnosed with BPD, SCH, MDD, BAP, and AD were compared on the internalized stigma of mental illness (ISMI) scale. The ISMI-total score was correlated with the subjective and objective evaluation of the disorder severity (clinical global impression), and clinical and demographic factors. Results: The self-stigma levels were statistically significantly different among the diagnostic groups (BPD 71.15±14.74; SCH 63.2±13.27; MDD 64.09±12.2; BAD 62.0±14.21; AD 57.62±15.85; one-way analysis of variance: F=8.698, df=183; P<0.005). However after applying the Bonferroni’s multiple comparison test, the only significant difference was between the BPD patients and the patients with AD (P<0.001). Stepwise regression analysis showed that the strongest factors connected with the higher level of self-stigma were being without partner, the number of hospitalization, and the severity of the disorder. Conclusion: The BPD patients suffer from a higher level of self-stigma compared to patients with AD. In practice, it is necessary to address the reduction of self-stigma by using specific treatment strategies, such as cognitive therapy. Keywords: self-stigma, borderline personality disorder, schizophrenia spectrum and related disorders, major depressive disorder, anxiety disorders, severity of the disorder